1999
DOI: 10.3758/bf03207713
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale databases of proper names

Abstract: Few tools for research in proper names have been available-specifically, there is no large-scale corpus of proper names. Two corpora of proper names were constructed, one based on U.S. phone book listings, the other derived from a database of Usenet text. Name frequencies from both corpora were compared with human subjects' reaction times (RTs) to the proper names in a naming task. Regression analysis showed that the Usenet frequencies contributed to predictions of human RT, whereas phone book frequencies did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For example, names are typically lower in overall frequency of use than other sorts of words (e.g., even James, a fairly high-frequency surname, is less commonly encountered than the biographical information is a student or the common noun house). Under this account, low word frequency, not status as a name per se, causes the increased difficulty in name memory (see Conley, Burgess, & Hage, 1999 for a discussion of name frequency). In addition, there is a greater ''set size'' of possible phonological sequences for names than there is for other types of words, and this wider variety of potential sound combinations might contribute to names' difficulty (e.g., Brennen, 1993).…”
mentioning
confidence: 99%
“…For example, names are typically lower in overall frequency of use than other sorts of words (e.g., even James, a fairly high-frequency surname, is less commonly encountered than the biographical information is a student or the common noun house). Under this account, low word frequency, not status as a name per se, causes the increased difficulty in name memory (see Conley, Burgess, & Hage, 1999 for a discussion of name frequency). In addition, there is a greater ''set size'' of possible phonological sequences for names than there is for other types of words, and this wider variety of potential sound combinations might contribute to names' difficulty (e.g., Brennen, 1993).…”
mentioning
confidence: 99%
“…While Rastle and Burke (1996) found advantages for prior processing of phonological information in terms of reducing TOTs, they found that asking participants to first rate how pleasant each of the words were (semantic processing), prior to retrieving them from definition questions, did not provide any extra advantage in reducing TOTs above and beyond simply reading the phonology of the TOT word. Cross and Burke (2004) showed that the lack of facilitation from prior processing of semantic information on TOT incidence also occurred for proper names. In this experiment, young and older adults (mean age 72) were first asked a question about a famous character (e.g., Eliza Doolittle), were subsequently shown a picture of the person depicting that famous character (e.g., a picture of Audrey Hepburn portraying Eliza Doolittle), and were asked to produce the name of the portrayer (e.g., Audrey Hepburn).…”
Section: Semantic Primingmentioning
confidence: 98%
“…When more phonological components are needed to retrieve the entire name phrase, there are correspondingly more opportunities for retrieval failures to occur, which explains why individuals tend to have more TOTs for targets who are known by three names (e.g., actor Sarah Jessica Parker) as opposed to just two (e.g., actor Julia Roberts; Hanley & Chapman, 2008;Stevenage & Lewis, 2005). Proper names are also generally accessed less frequently than nouns; even the most common names, like Smith, are accessed less often than other types of words, which makes the connections among conceptual, lexical, and phonological information within the proper name hierarchy comparatively weak and more prone to retrieval failures (e.g., Cohen & Burke, 1993;Conley, Burgess, & Hage, 1999).…”
Section: Explanation For the Vulnerability Of Proper Namesmentioning
confidence: 99%
“…When more phonological components are needed to retrieve the entire name phrase, there are correspondingly more opportunities for retrieval failures to occur, which explains why individuals tend to have more TOTs for targets who are known by three names (e.g., actor Sarah Jessica Parker) as opposed to just two (e.g., actor Julia Roberts; Hanley & Chapman, 2008;Stevenage & Lewis, 2005). Proper names are also generally accessed less frequently than nouns; even the most common names, like Smith, are accessed less often than other types of words, which makes the connections among conceptual, lexical, and phonological information within the proper name hierarchy comparatively weak and more prone to retrieval failures (e.g., Cohen & Burke, 1993;Conley, Burgess, & Hage, 1999).…”
Section: Explanation For the Vulnerability Of Proper Namesmentioning
confidence: 99%